Safety and efficacy of glucagon-like peptide-1 receptor agonists in patients with obstructive sleep apnea: a systematic review and meta-analysis of randomized controlled trials - Obieda Altobaishat; Ahmed Farid Gadelmawla; Elsayed Balbaa; Mustafa Turkmani; Mohamed Abouzid (European Clinical Respiratory Journal)
Background Obstructive sleep apnea (OSA) is a common condition affecting around one billion people worldwide. Emerging evidence from recent studies suggests that Glucagon-like peptide 1 receptor (GLP-1) agonists may reduce OSA severity. Hence, this meta-analysis aims to evaluate the efficacy and safety of GLP-1 agonists in patients with OSA.Methods Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, we searched four electronic databases (PubMed, EMBASE, Cochrane Library, Scopus, and Web of Science) to identify eligible studies reported up to 24 June 2024. Using Review Manager software, we reported outcomes as risk ratios (RRs) or mean difference (MD) and confidence intervals (CIs). The protocol for this review has been registered and published in PROSPERO with the ID (CRD42024562853).Results The meta-analysis included three randomized controlled trials with 828 patients. Pooled analysis of patients administered GLP-1 agonists or tirzepatide showed improvement in Apnea/Hypopnea Index (MD −16.57 events per hour, 95% CI [−27.41, −5.73], p = 0.003), weight reduction (MD −12.71%, 95% CI [−21.38, −4.03], p = 0.004), and systolic blood pressure (MD −4.93 mmHg,95% CI [−7.67, −2.19], p = 0.0004). Tirzepatide showed a reduction in high-sensitivity C-reactive protein (MD −0.89 mg/dl, 95% CI [−1.25, −0.54], p < 0.0001) and sleep apnea-specific hypoxic burden (MD −66.21%/min, 95% CI [−81.75, −50.67], p < 0.0001). Despite the heterogeneity observed in the AHI and weight, it was resolved, and the results were consistent. GLP-1 agonists/tirzepatide showed comparable outcomes concerning diastolic blood pressure (MD −1.34 mmHg, 95% CI [−2.80, 0.12], p = 0.07). No significant serious adverse events were observed for GLP-1 agonists/tirzepatide, but it was associated with a higher incidence of gastrointestinal adverse events.Conclusion GLP-1 agonists, including tirzepatide, improved Apnea/Hypopnea Index, weight, and systolic blood pressure in adults with moderate-to-severe OSA. However, the evidence remains limited to two published studies comprising three randomized controlled trials using different pharmacological agents. Consequently, further research is needed before firm conclusions can be drawn.